2021
DOI: 10.1183/23120541.00242-2021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the behaviour and health status of patients with COPD: results from the German COPD cohort COSYCONET

Abstract: BackgroundInfection control measures for COVID-19 might have affected management and clinical state of patients with chronic obstructive pulmonary disease (COPD). We analysed to which extent this common notion is fact-based.MethodsPatients of the COSYCONET cohort were contacted with three recurring surveys (COVID1, 2, 3 at 0, 3 and 6 months). The questionnaires comprised behaviour, clinical and functional state and medical treatment. The responses to the questionnaires were compared amongst themselves and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
(12 reference statements)
0
6
1
1
Order By: Relevance
“…Additionally, the vast majority of patients indicated that they adhered to one or more of the preventive measures. In a significant number of our patients, the physiotherapy training had been discontinued, which in the context of social distancing is understandable [ 7 ]. However, since exercise training is associated with increased physical activity and deconditioning may lead to increased dyspnoea, we believe this is a concerning development for patients with severe COPD [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the vast majority of patients indicated that they adhered to one or more of the preventive measures. In a significant number of our patients, the physiotherapy training had been discontinued, which in the context of social distancing is understandable [ 7 ]. However, since exercise training is associated with increased physical activity and deconditioning may lead to increased dyspnoea, we believe this is a concerning development for patients with severe COPD [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that immigrants and patients from low socioeconomic areas faced reduced healthcare access during the pandemic (16)(17)(18). The pandemic has also negatively affected care for patients with chronic conditions, such as chronic kidney disease, diabetes, and chronic respiratory conditions, leading to increase chronic disease burden and reduced access to primary care and other services (e.g., dialysis) (19,20). It is unknown whether the pandemic has led to worse ICU outcomes for these specific patient populations.…”
Section: Background and Rationalementioning
confidence: 99%
“…Entsprechend stellte sich die Frage, ob die mit COVID-19 einhergehenden Restriktionen zu einer Verschlechterung des klinischen Zustandes der Patienten geführt haben. Dies war, wenn auch in geringem Maße, der Fall, wobei Patienten der höchsten GOLD-Gruppe (D) und Frauen am stärksten betroffen zu sein schienen 66 .…”
Section: Ergebnisseunclassified